MENINGKATKAN KECERDASAN EMOSIONAL ANAK USIA 5-6 TAHUN MELALUI METODE BERMAIN PERAN DALAM KELOMPOK B DI TK ISLAM AL-IKHLAS BAGANSIAPIAPI - Linawati Linawati; Zulkifli N Zulkifli N; Nurlita Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background of this study is the lack of emotional intelegence of children through role play method. Based on that it is necessary to attempt to improve emotional intellegence is through role play. The purpose of this study was to determine the child’s emotional intellegence through role-play method, to determine the child’s emotional intellegence through methods play a role. This type of research is classroom action research conducted in 2 (two) cycles. Data collection tool used in this study is the group B consisiting of 4 girl and 6 boys. The results showed an increase from cycle I to cycle II. The increase occurred, ie from before the action to cycle I amounted to 29.97%, cycle I to cycle II amounted to 39.75% and from the prior cycle to cycle II at 81.65%. of the results of this study can be concluded that through role play can improve emotional intelligence in group B TK Islam Al-Ikhlas Bagansiapiapi Rokan Hilir.Keyword : Emotional Intelligence, Play a Role